5. Coregraphic Arts Education from the Intercultural Perspective - Todi Cristina (Sciendo, 2018)
Theatre, dancing and singing are arts born out of a common body that share the same idea and means of expression - the human body, these arts manifesting through the most important condition - the artist. The openings exhibited in the theatrical space, spiritless in some people, pragmatic in others, pass on the intimate message of dancing: substance, essence, density.